Aux guichets de l’inspection du travail - Anaïs Bonanno (La Nouvelle Revue du Travail)
Labour inspection agents are known for being empowered to conduct investigations regarding the application of law in workplaces. However, they also play a role in informing workers and employers about labour rights. In the French system of labour inspection, this function is performed by two offices: control agents, and information agents. For the latter, information is an exclusive function. How do information agents legitimate their activity, being part of Labour inspection without being empowered to intervene? The paper first outlines the bases of the moral division of labour between these two groups. Then it explores its effects on the information agents. The moral division of labour reaches its climax when information agents fail to redirect workers or employers to control agents, due to the latters’ overwork. Information agents thus become exposed to the users’ misunderstanding. This partial failure nonetheless gives to information agents the opportunity to intervene in the users’ professional situations even though they are legally not supposed to do so. They can therefore legitimize their professional activity.